Peran Kelekatan Ibu Terhadap Perkembangan Sosial Emosional Anak Usia Dini - Fredericksen Victoranto Amseke; Naisanu Florawati Naisanu; Uslina Mimin (Universitas Nusa Cendana, 2025)
Social emotional development is an important aspect that influences mother's attachment to early childhood. The aim of this research is to determine the influence of maternal attachment on the social emotional development of children aged 5-6 years. The method in this research is quantitative. The sampling technique was purposive sampling, namely children aged 5-6 years (class B). The respondents for this research were 60 children aged 5-6 years at TK Bethlehem Oesapa Barat, Kupang City. The data collection technique uses a questionnaire with instruments in the form of scales of maternal attachment and social emotional development. The maternal attachment scale developed by Armsden dan Greenberg (2009) is called the Inventory of Parent. The social emotional development scale developed by Squires, Bricker dan Twombly (2002) is called the social emotional development scale. The data analysis technique is simple linear regression. The results of these findings found that maternal attachment had a positive and significant effect on the social emotional development of children aged 5-6 years by 13.1%, which means that the better the maternal attachment, the better the social emotional development of early childhood. It is hoped that mothers can establish a safe and comfortable relationship with their children, understand the needs and characteristics of children which can influence mental health in the social emotional development of early childhood.